Key molecular processes of the diapause to post‐diapause quiescence transition in the alfalfa leafcutting bee Megachile rotundata identified by comparative transcriptome analysis. (3rd March 2015) - Yocum, George D.; Rinehart, Joseph P.; Horvath, David P.; Kemp, William P.; Bosch, Jordi; Alroobi, Rami; Salem, Saeed
Abstract Insect diapause (dormancy) synchronizes an insect's life cycle to seasonal changes in the abiotic and biotic resources required for development and reproduction. Transcription analysis of diapause to post‐diapause quiescent transition in the alfalfa leafcutting bee Megachile rotundata Fabricius identifies 643 post‐diapause up‐regulated gene transcripts and 242 post‐diapause down‐regulated transcripts. The log2 fold change in gene expression levels ranges from −5 to 7. Transcripts from several pivotal diapause‐related processes, including chromatin remodelling, cellular signalling pathways, microRNA processing, anaerobic glycolysis, cell cycle arrest and neuroendocrine control, are identified as being differentially expressed during the diapause to post‐diapause transition. In conjunction with studies from other insect species, the data indicate that there are several common mechanisms of diapause control and maintenance.